(untitled) (Economics and region, 2021)
The purpose of the article is an in-depth analysis of the scientific literature and systematization of the concept of "motivation", clarifying the nature and significance of staff motivation in enterprises of socio-cultural services and tourism. On the basis of the conducted research the own interpretation of the concept "motivation" is given. The key benefits provided by staff motivation to enterprises are presented. Theories of motivation, which can serve as a basis for building an effective system of motivation in the enterprises of socio-cultural service and tourism, are studied, their schematic grouping is given. According to the results of the analysis of the most common theories of motivation, a symbiosis of their provisions is highlighted, which forms the theoretical basis of the system of staff motivation at the enterprises of socio-cultural service and tourism.